Effect of Mediterranean Diet in Diabetes Control and Cardiovascular Risk Modification: A Systematic Review - Sleiman, Dana; Al-Badri, Marwa R.; Azar, Sami T. (Frontiers in Public Health, 2015)
Background Over the past few years, there has been a worldwide significant increase in the incidence of type II diabetes mellitus with both increase in morbidity and mortality. Controlling diabetes through life style modifications, including diet and exercise has always been the cornerstone in diabetes management. Increasing evidence suggests that the Mediterranean diet could be of benefit in diseases associated with chronic inflammation, including metabolic syndrome, diabetes, obesity as well as atherosclerosis, cancer, pulmonary diseases, and cognition disorders As a matter of fact, a number of studies addressed the relationship between Mediterranean diet and diabetes control. The result of these studies was conflicting. Some were able to elicit a protective role, while others showed no added benefit. As a result; we decided to conduct a systematic review to have a better understanding of the relationship between adherence to Mediterranean diet and diabetes control. Methods A systematic review was conducted on the effect of Mediterranean diet in diabetes control and cardiovascular risk modification as well as the possible mechanism through which this diet might exhibit its beneficial role. We did a comprehensive search of multiple electronic databases such as Medline, Google Scholars, PubMed, and the Cochrane central register data until May 2014. We included cross-sectional, prospective, and controlled clinical trials that looked at the associations between Mediterranean diet and indices of diabetes control such HbA1c, fasting glucose, and homeostasis model assessment, in addition to cardiovascular and peripheral vascular outcomes. Outcome/conclusion Most of the studies showed favorable effects of Mediterranean diet on glycemic control and CVD, although a certain degree of controversy remains regarding some issues, such as obesity. Important methodological differences and limitations in the studies make it difficult to compare results, thus further longer term studies are needed to evaluate the long-term efficacy of the Mediterranean diet along with the possibility of explaining its mechanism.